The Influence of Plasma Protein Glycation in Diabetes Mellitus Type 2 and its Complications (Medical Forum Monthly, 2020)
Objective: The present project was planned to study effect of Glycation in diabetic complications.Study Design: Correlational and experimental studyPlace and Duration of Study: This study was conducted at the DHQ Faisalabad and Allied hospital Faisalabad from March 2018 to April 2019.Materials and Methods: A total 100 patients were taken. They were grouped in 5, each having 20 patients. These groups were according to the complications, normal and normal diabetics. Blood samples of diabetic patients with and without complication were collected from D.H.Q and Allied Hospital Faisalabad. The information included age, sex, and duration, family history of diabetics, treatment status and diabetic control in relation to complications. (Neuropathy, nephropathy, foot ulcer, retinopathy) were taken by using a self-designed Performa. Specific techniques of spectrophotometer and software were used to analyze all the collected samples. The biochemical parameters were protein estimation, glucose estimation, determination of level of Glycation, determination of protein marker by SDS_PAGE analysis.Results: We have found levels of glucose, protein and Glycation for both normal and diabetic patients. Correlational analysis between glucose, and Glycation level showed positive outcomes r=0.4199 for normal subjects and r=0.242 for glycated. Analysis between protein and Glycation level for normal individuals was r=0.4977.After SDS-PAGE Analysis of diabetic patient's blood with complications and without complications and normal revealed a difference of migrating bands with molecular weights between 20 and 30. One faster migrating band was missing in diabetic patients with Ischemic heart disease and two bands were of less intensity in with neuropathy and foot ulcer of age 64 years. While the diabetic patients without complications and normal showed no missing band. So, our results show that some protein is missing in diabetic complications.Conclusion: Our results suggest that increased level of Glycation participate in long term complications.